Security through cooperation : to the same end - Kemp, Walter A. (Abingdon, Oxon ; New York : Routledge, 2022)
"This book makes the case for why cooperation is the key to security within and between states, and for dealing with complex threats and challenges to international peace and security. It argues that cooperation is not altruism or liberal internationalism, rather it is in the self-interest of states. Drawing on both theory and practice, it looks at how cooperation can be promoted within and between states as well as in the global community. It explains the concept of 'cooperative security' and its potential contribution to promoting integration against the current of fragmentation. Furthermore, the book explores the potential impact of technology on cooperation. It makes an urgent call for new ideas and approaches to encourage people and states to work together to deal with complex threats and challenges. This book will be of particular interest to students of diplomacy studies, foreign policy and International Relations, and to practitioners dealing with security issues"--
Preface -- Why Cooperate? -- Cooperation within Multiethnic States -- Cooperation between States -- Learning to Cooperate -- Institutionalizing Cooperation -- Cooperation for the Future -- Epilogue.
Includes bibliographical references (pages 118-120) and index.
Keywords: Security, International; Human security; Cooperation -- Political aspects; World politics; International relations -- Diplomacy; Security cooperation